Deoxynivalenol (Vomitoxin)-Induced Anorexia Is Induced by the Release of Intestinal Hormones in Mice - Yue, Jianming; Guo, Dawei; Gao, Xiuge; Wang, Jiacai; Nepovimova, Eugenie; Wu, Wenda; Kuca, Kamil (Toxins, 2021)
Deoxynivalenol (DON), also known as vomitoxin, is a mycotoxin that can cause antifeeding and vomiting in animals. However, the mechanism of DON inducing anorexia is complicated. Studies have shown that intestinal hormones play a significant part in the anorexia caused by DON. We adopted the "modeling of acute antifeeding in mice" as the basic experimental model, and used two methods of gavage and intraperitoneal injection to explore the effect of intestinal hormones on the antifeedant response induced by DON in mice. We found that 1 and 2.5 mg/kg·bw of DON can acutely induce anorexia and increase the plasma intestinal hormones CCK, PYY, GIP, and GLP-1 in mice within 3 h. Direct injection of exogenous intestinal hormones CCK, PYY, GIP, and GLP-1 can trigger anorexia behavior in mice. Furthermore, the PYY receptor antagonist JNJ-31020028, GLP-1 receptor antagonist Exendin(9-39), CCK receptor antagonist Proglumide, GIP receptor antagonist GIP(3-30)NH2 attenuated both intestinal hormone and DON-induced anorectic responses. These results indicate that intestinal hormones play a critical role in the anorexia response induced by DON.
Keywords: Animals; Eating; Female; deoxynivalenol; nechutenství; ženské pohlaví; piperaziny; intestinal hormones; Gastrointestinal Hormones; stravovací zvyklosti; gastrointestinální hormony; Mice; anorexia; proglumid; myši; přijímání potravy; peptidové fragmenty; Anorexia; receptory gastrointestinálních hormonů; trichothecene; Trichothecenes; Benzamides; Proglumide; Peptide Fragments; Feeding Behavior; benzamidy; Piperazines; žaludeční inhibiční polypeptid; Gastric Inhibitory Polypeptide; trichotheceny; mycotoxin; zvířata; Receptors, Gastrointestinal Hormone